Terminal power control method of power line carrier communication network based on adaptive hash function - Hong XUE; Jiahan WANG; Yuling SUN; Bo HAN; Yubai XIAO (Dianxin kexue)
In the control of network terminal power, due to the overall low analysis of network state, the adaptive regulation ability of communication network terminal power is poor.Therefore, the power line carrier communication network terminal power control method based on adaptive hash function was proposed.Considering the dynamic fluctuation of the actual operating state of the power line carrier communication network, the adaptive mechanism was set for the hash function, and the adaptive hash function was constructed for the original running state data, and the final hash value was obtained in the variable chaotic mapping system.In the power control stage of the power line carrier communication network terminal, the communication network terminal was affected by the interference of other communication network terminals, and it was used as the input value of the adaptive hash function to realize the power control of each communication network terminal.In the test results, the proposed control method not only effectively reduces the increase range of network terminal power under constant communication conditions, but also effectively reduces the network terminal power output under dynamic communication conditions, which has a high adaptive adjustment ability.